Identifikasi Bakteri Escherichia Coli Pada Ulkus Diabetikum Studi di Klink Kanazawa Pontianak Menggunakan PCR gen 16S rRNA - Nurhidayatulloh, Ariffialdi; Ramadhani, Natasya Intan; Abidin, Khoirul Rista; Suwandi, Edy; Salsabila, Aisha; Widodo, Kaltri; Andriani, Lulu; Hamidah, Najwa; Wulandari, Tri (poltekkes kemenkes pontianak, 2025)
Diabetes mellitus can lead to complications such as ulcers that are highly susceptible to bacterial infection. Escherichia coli is one of the pathogenic bacteria commonly found in diabetic foot ulcers. Accurate detection of E. coli species is essential to support appropriate infection management, and one of the reliable methods is Polymerase Chain Reaction (PCR) targeting the 16S rRNA gene. This study employed a descriptive design with an accidental sampling technique. Samples were obtained from swab specimens of diabetic foot ulcer patients. The procedures included culture on Eosin Methylene Blue (EMB) agar, Gram staining, bacterial DNA isolation, PCR amplification of the 16S rRNA gene, electrophoresis for visualization of PCR products, and sequencing for species confirmation. Based on the results of the study involving 30 diabetic foot ulcer patients at Kanazawa Clinic Pontianak, culture analysis showed that 4 isolates were positive for Escherichia coli. Gram staining further confirmed the presence of E. coli by demonstrating its characteristic morphology. The PCR results visualized through electrophoresis showed that 4 samples (13.3%) were positive for Escherichia coli based on the 16S rRNA gene, indicated by the presence of DNA bands at approximately 1500 bp. Sequencing analysis further confirmed the isolates as Escherichia coli with 99% similarity.